The meteorite collection of the Museo Nazionale dell’Antartide in Siena – December 2002 update - FOLCO, LUIGI; Rastelli N. (2002)
The updated (December 2002) catalogue for the meteorite collection of the Museo Nazionale dell'Antartide is presented. The collection primarily contains meteorites recovered from Antarctica by the Italian Programma Nazionale di Ricerche in Antartide, but also includes specimens from various locations around the world. The collection totals 983 specimens representing 28 876 g of extraterrestrial material of asteroidal and planetary origin, including 920 chondrites, 51 achondrites, 3 stony-iron meteorites and 9 iron meteorites.